Systematic studies of the genus Aegialomys Weksler, Percequillo and Voss, 2006 (Rodentia: Cricetidae: Sigmodontinae): Annotated catalogue of the types of the species-group taxa - Prado, Joyce Rodrigues Do; Percequillo, Alexandre Reis (Zootaxa, 2016)
The genus Aegialomys was described to encompass the former Oryzomys xanthaeolus group, and includes nowadays two species: A. xanthaeolus and A. galapagoensis. Although not very confusing, the taxonomic history of the genus is long, comprising the description of five nominal taxa along the last 180 years: Mus galapagoensis Waterhouse, 1839; Oryzomys bauri Allen, 1892; Oryzomys xanthaeolus Thomas, 1894; Oryzomys  baroni Allen, 1897; and Oryzomys  xanthaeolus ica Osgood, 1944. Here we gathered and documented all available information about the type material of Aegialomys on which the species names were based, re-described their morphometric and morphological characters, commented their synonyms and taxonomic history, and compiled information about type localities. Additionally, we established a neotype for O. bauri in order to define the nominal taxon objectively.